Matthew's presentation of the son of David: Davidic tradition and typology in the gospel of Matthew - Zacharias, H. Daniel (Criminal Practice Ser., 2016)
Cover -- Half-title -- Title -- Copyright -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1: Introduction -- 1. Previous Work on Davidic Tradition in Matthew -- 2. Thesis -- 3. Contribution -- 4. Methodology -- 5. Approach -- 6. A Sketch of Davidic Messianism at the Turn of the Era -- Chapter 2: Enter the Son of David: Matthew's Incipit and Genealogy -- 1. Matthew's Incipit -- 2. The Significance of David in the Genealogy -- 3. Conclusion -- Chapter 3: Assuming the Throne: Establishing Jesus as the Son of David -- 1. Mary and Joseph -- 2. Matthew's Isaiah 7 Quotation